Physicochemical properties of modified soybean-flour adhesives enhanced by carboxylated styrene-butadiene rubber latex. (April 2016) - Li, Hongyan; Kang, Haijiao; Zhang, Wei; Zhang, Shifeng; Li, Jianzhang
Abstract: As an abundant and renewable resource with high biodegradability, soybean-flour (SF) adhesive has aroused further interest by many researchers. Modified soybean-flour (MSF) adhesives with high solid content offer great potential as alternatives to petroleum-based adhesives. The objective of this study was to investigate the physicochemical properties of MSF adhesives modified by carboxylated styrene-butadiene rubber latex (XSBRL). The solid content, viscosity, adhesion, structural change, and morphological properties of the MSF/XSBRL adhesives were characterized in detail. Viscosity of the MSF adhesives was reduced remarkably and the dry and wet shear strengths of the MSF/XSBRL adhesives were enhanced with the increased addition of XSBRL, which acted as both a viscosity reducer and enhancer. X-ray diffraction patterns and morphological images indicated that the cured adhesives became more compact and homogeneous (following XSBRL modification), which prevented damage by moisture or water. Attenuated total reflection-Fourier transformation infrared spectroscopy showed that no apparent chemical reaction occurred between XSBRL and the MSF adhesives. The introduction of polar carboxyl groups contributed to high adhesion, superior emulsibility and good flowability of XSBRL, which improved the adhesion performance and reduced the viscosity of the MSF adhesives.